Submerged Macrophytes Exhibit Different Phosphorus Stoichiometric Homeostasis - Li, Wei; Li, Yujie; Zhong, Jiayou; Fu, Hui; Tu, Jie; Fan, Houbao (Frontiers in Plant Science, 2018)
Phosphorus (P) is a limiting element in many aquatic ecosystems. Excessive P input often leads to cyanobacterial bloom, thus triggering ecological imbalances and a series of environmental problems. Submerged macrophytes have a strong ability to absorb P and play important roles in maintaining aquatic ecosystem functions. However, the degree to which submerged macrophytes maintain their tissue P contents in various nutrient levels and the corresponding influencing factors are still not very clear. In this study, the stoichiometric characteristics and stoichiometric homeostasis of P in the aboveground and belowground parts of three submerged macrophytes, Vallisneria natans (Lour.) Hara, Hydrilla verticillata (L. f.) Royle and Ceratophyllum demersum (L.), with great differences in growth forms, were studied under different growth times and nutrient levels via laboratory experiments. The results showed that the water conductivity, turbidity, and chlorophyll content increased significantly with the increasing nutrient levels. The variation of species, organ, growth time, and nutrient level could significantly affect the P contents of submerged macrophytes. Among these factors, the variance contribution rates caused by the differences of nutrient levels in water column were the highest at more than 50%. The P stoichiometric homeostasis index (HP) in the belowground parts of the three submerged macrophytes was higher than that of the aboveground parts. The HP decreased by the growth time; the HP of V. natans was significantly higher than those of H. verticillata and C. demersum. In summary, the P stoichiometric homeostasis in submerged macrophytes could reflect their responses to environmental changes, and the P content of submerged macrophytes was an indicator of the bioavailability of external P. H. verticillata exhibited a high growth rate and a high accumulation of P content, making it the most suitable species in this study for removing large amounts of P from water in a short term.